Developing 21st Century Skills through the Make-a-Match Method in Reaction Rate Learning - Sari, Sari; Khoerunisa, Khoerunisa (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
The 21st century revolution demands individuals enhance their quality to thrive in a globalized world. Consequently, mastering critical thinking, creativity, collaboration, and communication (4C) skills has become a necessity for success in this context. This study aims to analyze students’ activities during the Make a Match learning process assisted by question cards and the improvement of students’ 4C skills at each stage of the process. A mixed-method approach was employed, combining qualitative and quantitative methods. The qualitative approach described student activities using observation sheets, while the quantitative approach applied a pre-experimental one-shot case study design. The participants were 26 science class XI students from SMA Darussalam Wanaraja Garut. Instruments included learning descriptions, observation sheets, student worksheets, and post-test questions. The results indicated that overall, student activity reached 96.75%, categorized as very good, with an average activity score of 3.87. The highest and lowest average activity scores were 4 and 3.5, respectively. The average 4C skills score, derived from activities and worksheets, was 91.125, also categorized as very good. Creative skills achieved the highest average score of 97.5 (very good), while critical thinking scored 87 (good). Hypothesis testing showed a significant positive influence of the Make-a-Match method on students’ 4C skills. The findings underscore the effectiveness of the Make-a-Match method in fostering 4C skills, offering valuable insights for innovative learning strategies in chemistry education.